Evaluating the Economic Efficiency of Crop Production in the Floodplain During the Dry Season in Chulkiri District, Kampong Chhnang Province - Mengponleu Chea; Mardy Serey; Oudam Ponh (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: This study aims to assess the status of crop production and evaluate the costs, benefits, opportunities, and challenges along Tonle Sap Lake during the dry season. Methodology: Data were collected from 47 farmers, 10 vendors, and four local authorities through random interviews followed by questionnaires. The cost-benefit ratio, net present value (NPV), and sensitivity analyses were conducted, assuming a 9% cost overrun and a 5% yield decrease for analysis data. Main Findings: The study found, that farmers employ crop rotation and expertise from nearby farmers to grow beans, corn, sweet chilli, and melon from December to August. Floodplain crop production is moderately profitable, despite a 10% increase in total costs, with labor, irrigation, fertilizer, weeding, and pesticides being the high expenses. Challenges such as labor scarcity, financial literacy deficits, pest management issues, falling crop values, climate variability, and insufficient seed storage further complicate floodplain agriculture. Novelty/Originality of this study: This research explores floodplain farming's financial efficiency, and sustainability, utilizing cost-benefit analysis, sensitivity analysis, and qualitative evaluations to address Cambodia's unique agricultural challenges in the floodplain area.